Födelsevikt och tidig tillväxt hos nyfödda lamm - Nygren, Sofia (2010)
Sheep production is the only animal production in Sweden that is increasing. Therefore, increasing knowledge of the production is of great interest. In order to run a viable sheep production, producers needs to be successful in the breeding of the animals and achieve an economic surplus in the end. Lambs that are born healthy and vital have greater conditions to perform high lamb weight gains and thus a successful production. There are many factors affect the survival, birth weight and early weight gain of the new born lamb. The most important factors regarding the maternal influence and the environmental factors that affect the lambs survival and early life weight gain was explored in this paper. Weight at birth is positively correlated to survival, weight gain, adult weight and maternal traits. Litter size affects the birth weight and is explained by that the uterus is a limited space. Birth weight of lambs is lower in first parity ewes. Birth weight of lambs increases with the ewe’s age up to the fourth parity when it declines again. The foetus grows rapidly during the last weeks of gestation and the newborn lamb weight can be affected by feeding. Feeding regime in early gestation does not affect the growth of the foetus. The milk production of the ewe is of great significance for the lambs’ early weight gain. Lambs that have restricted access to milk in early life have a low correlation between birth weight and early life weight gain. A minor investigation was made to study the influence of birth weight on early weight gain in post natal lambs. The study included 53 lambs of different breeds. The weights of the lambs were registered at as close to birth as possible and as close to 120 hours after the first occasion as possible. An hourly weight gain was calculated in order to calculate a corrected weight at 120 hours. Litter size, sex of the lamb, age and the maternal behavior of the ewe and occurrence of complications during parturition were also registered. The study showed that birth weight affects the early weight gain. Lambs with higher birth weights had higher early weight gains than lambs that were smaller at birth. The results confirmed earlier studies. A likely explanation is that small lambs have a lower early weight gain due to their smaller potential to feed as much as heavier lambs. However, lambs which were smaller at birth had relatively, to the birth weight, a higher growth rate than the heavier lambs. The study also showed that male lambs were heavier and had a higher weight gain than female lambs. Triplets had lower birth weights and grew less than twins and single born lambs. There was only a marginal difference between twins and single born lambs. Adult ewes had the heaviest lambs and the highest weight gains of their lambs. Crossbreeds lambs had higher weights at birth than the purebreds. The study suffered from the relatively low number of lambs which makes extensive conclusions difficult to make except for the correlation between birth weight and early weight gain. It is suggested that birth weight and early weight gain can be used for selecting ewes in the herd as this parameter may well reflect the ewes’ success potential, including, foetus growth, maternal instincts and behaviour and milk production. But this has to be further investigated.